(untitled) (Revista Latinoamericana de Estudios del Discurso, 2020)
Serrano, María José (2006). Gramática del discurso. Madrid: Editorial Akal. 185 pp. ISBN- 10: 84-460-2354-8, ISBN 13: 978-844-60-2354-8.